Changing rooms : Handy Andy's Weekend Workbook : Step-by-Step projects from the Hit TV Series - Kane, Andy and Short, Chris (London BBC, 1998)
If you are full of creative ideas but have never held a hammer in your life and if you are the kind of person who thinks a screwdriver is a type of cocktail, then this book is for you! The irrepressible handyman of the BBC TV hit show Changing Rooms, Handy Andy demonstrates simple but stunning changes you can make to your home in no time at all. With over thirty imaginative and inexpensive projects, ranging from stylish shelving to practical splashbacks, and from fake wall panelling to fancy radiator covers, Handy Andy's Weekend Workbook has practical solutions for every nook and cranny of your home. Each project is accompanied by step-by-step illustrations, Andy's complete idiot-proof instructions and a full list of all the tools and materials needed to finish the job. Andy also includes great advice for every do-it-yourself novice, including essential techniques, how to build up a basic toolkit, and what type of timber to work with. So, even if your practical skills are non-existent and you don't know your mole grips from your mitre block, with Handy Andy you'll soon be in do-it-yourself heaven.
Include Color Illustration and Index
Keywords: Do-it-yourself work -- Dwellings--Maintenance and repair -- Interior decoration